Different Masters' Educational Methods on the Same Problem Based on the Present Situation of Vocal Education——Take 8 videos of 6 vocalists as an example - Feng, Chenyang (Transactions on Social Science, Education and Humanities Research, 2024)
The master class in vocal teaching has a significant impact on the improvement of students' vocal skills. This study aims to analyze the similarities and differences in vocal teaching between China and Western countries by comparing videos of master classes, and explore the cultural and societal reasons behind these differences. Six master classes from renowned vocal masters from both China and Western countries were selected as research samples. The analysis was conducted using a framework that includes cultural background and traditions, teacher-student relationships and interactions, and music theory and technical teaching. The analysis revealed that similarities in vocal teaching between China and Western countries include aspects such as expanding educational enhancements, demonstration and imitation, and personalized teaching. Differences were observed in warm-up exercises before singing, the timing of raising questions during singing, and the overall atmosphere of the class. Based on these findings, it is proposed that future vocal teaching should follow a teaching approach of "question-exploration-communication," preserving the strengths of existing educational models while learning and incorporating advanced aspects of Western vocal education.